Engineering of near-PAMless adenine base editor with enhanced editing activity and reduced off-target - Xiaofang Cao; Junfan Guo; Shisheng Huang; Wenxia Yu; Guanglei Li; Lisha An; Xiangyang Li; Wanyu Tao; Qing Liu; Xingxu Huang; Xiaohua Jin; Xu Ma (Elsevier, 2022)
About 47% of pathogenic point mutations could be corrected by ABE-induced A·T-to-G·C conversions. However, the applications of ABEs are still hindered by undesired editing efficiency, limited editing scopes, and off-targeting effects. Here, we develop a new adenine base editor, by embedding TadA-8e monomer into SpRY-nCas9, named as CE-8e-SpRY, which exhibits higher activity at NRN than NYN PAMs favored by SpRY nuclease. CE-8e-SpRY could target nearly all genomic sites in principle and induces the highest targeting efficiency among tested SpRY-based ABEs. In addition, CE-8e-SpRY also shows reduced RNA and DNA off-targeting activities. With optimized sgRNAs, CE-8e-SpRY induces efficient or desired target editing at some disease-relevant loci where conventional ABEs were unable to induce precise and satisfied editing. Taken together, our CE-8e-SpRY could broaden the applicability of ABEs in correcting or introducing pathogenic point mutations.